Women and the Informal Economy in Urban Africa: From the Margins to the Centre - Baker, Lucy (The International Journal of Sociology of Agriculture and Food, 2015)
Mary Njeri Kinyanjui provides a feminist, post-colonial and post-modern analysis of the informal economy of Nairobi, Kenya. Kinyanjui refreshingly brings to light a positive outlook of the contribution of women to Nairobi’s informal economy that provides revenue, employment and a grass-roots strategy against poverty. The author makes a clear call for African cities to de-masculinize and to Africanize. Documenting a case study of women operating in Taveta Road, Kinyanjui discovers a change in the demographic of women that are involved in informal economies in Nairobi since earlier studies of the 1990s. Not only are the characteristics of these women changing, but also the spaces they now occupy. This is the crux of Kinyanjui’s writing; that women who have been excluded by a modernist and predominantly male approach to urban planning have struggled from the periphery of the city to its core, and in doing so have made their presence in a masculine and elitist city centre.